Operator versus material influence on film thickness using adhesive resin cement or pre‐heated resin composite. Issue 3 (1st December 2022) - Teyagirwa, Prudence‐Felix; Aquin, Claire; Kharouf, Naji; Roman, Tatiana; Senger, Bernard; Reitzer, François; Etienne, Olivier
Abstract: Objective: There is a growing interest in using pre‐heated composites instead of dual‐cured cements when luting indirect restorations. This study evaluated the film thickness obtained from two pre‐heated composites and two resin cements, by two different operators. The influence of the materials and the level of expertise of the operator were analyzed. Materials and Methods: Forty specimens of human dentin and composite discs were prepared and divided into four groups depending on the luting process. Each group was randomly equally divided to be handled by two operators with different levels of experience. Two of the initial four groups were luted using dual‐cured cements and the two remaining groups using light‐cured pre‐heated composites. Specimen discs were cut after luting, and film thickness was measured using a Digital microscope. Data were analyzed using a 2‐way ANOVA with the Holm‐Sidak pairwise multiple comparison procedure ( p  < 0.05). Results: Mean film thickness ranged from 156.16 ± 4.7 to 33.82 ± 0.7 μm. Significant differences ( p  < 0.001) were noticed between expert and novice results with pre‐heated composites. Conclusion: Within the limits of this study, using pre‐heated composites as a luting cement requires a better level of expertise to achieve a clinically acceptable film thickness. Clinical Significance: Using pre‐heated composites as luting agent for indirect restorations requires an experimented skill level to achieve a clinically recommended film thickness.